Optimering av SNCR-system i en biobränsleeldad panna : möjligheter till minskade NOx-utsläpp för ENA Energi - Björk, Anna (SLU/Dept. of Energy and Technology, 2008)
Emission of nitrogen oxides as well as carbon monoxides is an inevitable result of combustion. A Swedish law "Law of environmental fee for emissions of nitrogen oxides as a result of energy production" (lagen om miljöavgift på utsläpp av kväveoxider vid energiproduktion (SFS 1990:613)) controls the emission of NOx from energy production by a system of fees. The system has resulted in a strong approach toward less emissions of NOx among the energy production plants. High emission levels, today exceeding 52 mg/MJsupplied fuel, leads to costs for energy production companies. This paper examines possibilities to reduce the emissions of NOx by optimization of the SNCR-technique in a biofuel fired heat and power plant. SNCR (Selective Non Catalytic Reduction) involve supply of an NOx reducing reagent in the furnace.